Fault Tree Analysis of Increased Pressure Drop in Hydrotreater Reactor - Pratiwi, Zahru Wilda; Nugroho, Budi Sulistiyo; Safitri, Lian; Jalil, Abdul; Trihadi, Wanda; Ramli (Catalyx : Journal of Process Chemistry and Technology, 2024)
The treating stage in a Catalytic Reforming Unit (CRU) is a critical process to ensure the longevity and efficiency of the reforming catalyst. However, anomalies like sudden and significant increases in reactor pressure drop, as observed in this case, can disrupt operations and reduce the unit's overall performance. It is crucial to identify the root cause of the observed pressure drop anomaly using the Fault Tree Analysis (FTA) method to systematically investigate the issue from multiple perspectives, enabling the identification of both minor and significant contributing factors. The FTA results indicate that external debris introduced during a recent catalyst changeover (COC) activity is the most likely cause. This allegation is supported by the analysis of equipment operation data and feed condition records, which did not reveal any significant changes. Given the absence of internal factors, the external influence of the COC activity emerges as the primary explanation for the pressure drop increase. To prevent similar occurrences in the future, it is crucial to implement rigorous cleaning and inspection procedures during turn-around (TA) activities to minimize the risk of debris entering the system. Monitoring reactor pressure drop and feed quality can also help detect and address potential issues early on. By taking proactive measures, the reliability and efficiency of the treating stage can be maintained, ultimately improving the overall performance of the CRU.